Predictors of primary school teachers’ self-efficacy beliefs for inclusive education - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Frontiers in Education, 2024)
Introduction: Teachers' self-efficacy is considered to be an essential personal resource which underlies the successful implementation of inclusion. The development of self-efficacy is supposedly linked to four main sources: Mastery and vicarious experiences, verbal persuasion, and physiological and affective states. Notwithstanding the importance of high self-efficacy beliefs, only few studies consider the impact of the individual sources on inclusion-related efficacy beliefs and thereby point out possible ways to promote teachers' self-efficacy. Methods: Therefore, we investigated the effect of the assumed four sources on the basis of a sample of N = 355 teachers that work in 'inclusive' primary schools. Results: Results from structural equation modelling highlight the importance of the supposed predictors of self-efficacy and in particular of teachers' own experiences. Self-efficacy in turn proved to be a significant predictor of teachers' willingness to implement inclusive education.